HIGH-YIELD REDUCTION OF 2-O-TRIFLUOROMETHANESULFONATE ESTERS OF ALPHA-HYDROXYLACTONES TO THE CORRESPONDING 2-DEOXYLACTONES BY LITHIUM IODIDE TRIHYDRATE - Elliott, R; Fleet, G; Gyoung, Y; Ramsden, N; Smith, C (1990)
Reaction of 2-O-trifluoromethanesulphonate esters of 1,4- and 1,5-α-hydroxy lactones with lithium iodide trihydrate in tetrahydrofuran gives good to excellent yields of the corresponding 2-deoxy lactones. © 1990.